Transactional interaction between computer salespersons and customers at a computer retails shop - Phe, Siaw Ching (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study examines transactional interaction between computer salespersons and customers at a computer retail shop. It is concerned with investigating how people in multilingual speech communities make appropriate language choices in first -time encounters with unfamiliar people, specifically in the context of a computer retail shop. The objectives of the study were: (1) to identify language choices of computer salespersons in interactions with customers, (2) to determine uncommon and inappropriate language choices and the context in which they occur, (3) to examine the responses to the uncommon and inappropriate language choices including how inappropriate languages choices are repaired, and (4) to examine the structure of the transactional conversations.To achieve these objectives, a computer retail shop was identified in Kuching, where salespersons and customers are from diverse language and cultural background.The techniques used for data collection were participant observation, audio recording and semi-structured interview. A total of 114 transactional conversations were observed, recorded and transcribed.The findings revealed that the common languages used included Local Malay, Mandarin, Bahasa Malaysia, English, Hokkienand Hakka. The inappropriate language choices occurred because of misjudgement of the customers’ language repertoire.When the customers gavea strange look and replied in their preferred language, the salesperson quickly repaired the situation by switching to their preferred language.Some of the stages in their structure are obligatory for instance, ‘Sales Request’ and ‘Purchase’in buying transactions. Others such as ‘Greeting’, ‘Sales',' Enquiry’and‘Finis’ are optional. The findings provided insights into the languages used for transactional purposes in a multilingual speech community.